An Ecological Approach to Modeling Vision: Quantifying Form Perception Using the Circle Map Equation. Issue 1 (2nd January 2020) - Munion, Ascher; Butner, Jonathan; Stefanucci, Jeanine; Geuss, Michael; Story, T. N.
Abstract: Object perception occurs within a dynamic world, where the environment and the observer (both body and eyes) are continually moving, shifting and changing. We seek to characterize and quantify this process from a perspective accounting for the interconnected system of motion in the environment, the perceiver and the eye, unfolding through time. Specifically, we build a mathematical representation for object perception based off the circle map equation. We describe an interaction between the eyes' movement and the movement in the world, in order to better understand how those work together to result in perception. Across three experiments, we show that the stability of the relationship between object perception and complex eye movements can be perturbed and will have a predictable response to said perturbations. In so doing, we provide a different context – a dynamical systems framework – under which we can begin to consider the ecological validity of visual perception models, while recognizing the degree to which the visuo-spatial world is continuously being perturbed and disrupted. In fact, we postulate that such perturbations are capitalized on by the perceptual system, contributing to accurate object and motion identification.